Influence of seasonal phytodetritus deposition on biogenic silica dissolution in marine sediments--Potential effects on preservation - Gallinari, Morgane; Ragueneau, Olivier; Demaster, D.; Hartnett, H.; Rickert, D.; Thomas, C. (Deep Sea Research Part II: Topical Studies in Oceanography, 2008)
International audience The deposition of fresh phytoplankton detritus (phytodetritus) following phytoplankton blooms may influence biogenic silica (BSi) dissolution in marine sediments. We studied BSi dissolution properties before, during, and after periods of phytodetritus deposition during time-series field programs in the abyssal North Atlantic (the BENGAL project), and on the West Antarctic Peninsula Shelf (the FOODBANCS project). Dissolution experiments, performed by means of flow-through reactors, showed temporal variations in the dissolution properties of BSi in the sediment column after phytodetritus deposition. This non-steady-state character of benthic silica dynamics is an important aspect of pelagic-benthic coupling. The last FOODBANCS cruise occurred after a phytodetritus deposition event, and yielded high pore-water dissolved silica (DSi) concentrations and DSi effluxes in the upper centimetres of the sediment column, suggesting a rapid turnover of recently deposited siliceous material. Higher dissolution rates were measured in the phytodetritus-rich sediments relative to surface sediments collected during previous seasons on earlier FOODBANCS cruises. During the BENGAL project, high dissolution rates were measured at depth in the sediment column only after a summer phytodetritus deposition event. In the highly detrital sediment matrix of the abyssal North Atlantic Ocean, resolution of increased dissolution rates and experimental artefacts of the flow-through reactors can be difficult because of the low abundance of BSi. Depending on the sediment matrix, bioturbation can play a crucial role in transporting fresh BSi particles to depth, where DSi concentrations are close to experimentally determined BSi solubilities. The potential impacts of such processes on BSi preservation are discussed. We suggest that future models of BSi early diagenesis should include the rapid mixing of freshly deposited particles if we want to describe further the preservation of BSi in marine sediments.